PENERAPAN METODE MAKE A MATCH BERBANTU MEDIA VISUAL PADA MATERI LITOSFER UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Reni, Reni (STAI Hubbulwathan Duri, 2019)
This study aims to determine the effect of using the make a match method in visual media to improve student learning outcomes. This study is a classroom action research (CAR), which consists of four phases of activity, namely planning, action, observation and reflection stages for each cycle. The implementation of the activity stages is carried out in 2 cycles. The study is conducted in the even semester of the 2018/2019 school year from January to February 2019. The first cycle was held in the third and fourth weeks of January, and the second cycle was held in the fifth week of January and the first week of February. This study was conducted in class X MIPA 2 in SMA N 1 Pangkalpinang. Preliminary tests were carried out before the first training cycle and completed in order to describe the initial conditions of the students, prior to taking any action after the assignments completed with the assessment tasks by writing tests for each cycle.The results of the study show that the initial abilities of the students before starting the action were at an average value of 65 and the percentage of completeness of 35.48%. At the first cycle, there was an increase in the mean value to 73, with the completeness percentage of 64.52%. There were several evaluations from the first cycle, including time management, addition of intergroup discussions, and rules of the game. This evaluation was used as the basis for improvement in the cycle 2, obtaining the average value to increase to 80 and the completeness percentage reached 100%. The value and completeness, as well as the student activity increased in the second cycle, from those at the first cycle. Based on these results, the study concluded that the use of make a match method combined with the visual media improved the student learning outcomes.